Impact of Pretreatment With Acid and Ultrasound on the Production and Characteristics of Goat Skin Gelatin - Muhamad Hasdar; Sitthipong Nalinanon; Chodsana Sriket (My University, 2024)
Goat skin is a potential raw material source for gelatin production using acid-ultrasound pretreatment. The objective of this study was to investigate the use of ultrasound in combination with acid pretreatment for the preparation of goat skin gelatin. Gelatin was extracted from goat skin using different pretreatments: acetic acid (T1), acetic acid followed by ultrasound (20 kHz and 750 W) (T2), and without pretreatment (T0). The results showed that the combination of acetic acid and ultrasound pretreatment significantly impacted the quality of the resulting gelatin. The study results showed an increase in yield (9.24 to 25.48%), hydroxyproline content (102.07 to 231.31 mg/g), gel strength (4.76 to 197.62 g), viscosity (6.80 to 48.00 cP), melting point (32.47 to 35.85 oC), EAI (18.24 to 23.58 m2/g), and ESI (24.90 to 62.63 min). However, there was a decrease in pH, the value of color L*, and turbidity. The SDS-PAGE patterns showed differences in molecular weight distribution due to variations in pretreatment. All gelatin samples exhibited α1 and α2 chains as the predominant components. Interestingly, the ultrasound effect highlighted the β-chain more boldly compared to other pretreatments. FTIR spectroscopy analysis shows changes in molecular interactions due to acetic acid pretreatment followed by ultrasound, which results in shifts in the Amide A, Amide B, Amide I, Amide II, and Amide III groups. Ultrasonic treatment caused more dense and disturbed structures in the sample. Therefore, the combination of acetic acid and ultrasound pretreatment yielded the superior properties of goat skin gelatin.
Keywords: Gelatin; Collagen: Extraction and Characterization